Peran Orang Tua Mendidik Anak Berprestasi di Bidang Akademik Kelas Tinggi di SD Negeri No.113/IV Kota Jambi - Ishak Muhammad; Dumaria Ike Juniati P (Jurnal Gentala Pendidikan Dasar, 2016)
The purpose of this study reveals the role of parents in educating children to achieve achievements in their academic fields. The population of this study were students of grades IV, V, and VI in Public Elementary School No.113 / IV Telanaipura, Jambi City and the sample was 15 outstanding children along with the parents of each child and each of them took only 5 achievers who were made sample. Instrument in data knowledge used interviews with parents of children and documentation in the form of data from mid semester grades IV, V, and VI report cards in odd semester along with photos of high achieving children who got grades 1 to 5. Data analysis techniques used were qualitative descriptive analysis . The results of research conducted on parents of high-achieving students in grades IV, V, and Vi at Public Elementary School No.113 / IV Telanaipura, Jambi City, are known that the role of parents is very important for the success of children in school, namely in the process of achieving these achievements. their children develop the potential of knowledge that children have, through the role of these parents children get the attention that parents should be given to be able to educate their children better in the process of achieving achievement in school. The conclusion of this study is that the role of parents in educating their children to achieve achievements in school is in good quality it can be said that 80% of parents strongly support children by instilling discipline, becoming motivators, supporters, and facilitators for their children.